ABOUT CLINICAL WORK IN SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE IN 2013 - M. L. Rogal (Неотложная медицинская помощь)
About clinical work in Sklifosovsky research Institute for Emergency Medicine in 2013.